High Potential of Aerosol‐Made 3D Graphene‐Based Composites for Enhanced Energy Storage. Issue 9 (20th March 2019) - Kim, Sun Kyung; Ha, Taehyeong; Lee, Chongmin; Chang, Hankwon; Jang, Hee Dong
Abstract: Recently, many researchers have developed advanced energy storage and energy conversion systems to address the increased demand for energy resources. The performance of these electrochemical energy storage and conversion devices depends considerably on the properties of their unique electrode materials. Among electrode materials, graphene (GR) has attracted much attention due to its unique properties of high flexibility, a large specific surface area, and superior electric conductivity rates that are well‐suited to energy storage systems. Specifically, aerosol‐made 3D GR composites are known to be more resistant to compressive forces such as paper balls owing to their stronger and harder compressive tolerance levels and higher and more stable surface areas compared to 2D GR sheets. These unique properties of 3D GR composites result in enhanced electrochemical performances for energy storage systems. This review focuses on recent studies of aerosol‐made 3D GR‐based composites for energy storage systems such as supercapacitors, lithium‐ion batteries, and sodium‐ion batteries. Abstract : Aerosol‐made 3D graphene (GR)‐based composites are known to be promising materials with many advantages that can be applied to energy storage devices. As‐prepared composites show enhanced electrochemical performances for energy storage systems. This review introduces recent studies focusing on aerosol‐made 3D GR‐based composites for various energy storage systems such as supercapacitors, lithium‐ion batteries, and sodium‐ion batteries.